Evaluation of the predictive value of coronary artery calcium score for obstructive coronary artery disease in asymptomatic Korean patients with type 2 diabetes mellitus. Issue 2 (March 2015) - Won, Ki-Bum; Chang, Hyuk-Jae; Niinuma, Hiroyuki; Sung, Jimin; Shin, Sanghoon; Cho, In-Jeong; Shim, Chi-Young; Hong, Geu-Ru; Kim, Young Jin; Choi, Byung-Wook; Chung, Namsik
<x xml:space="preserve">Abstract</x> Background Compared with coronary computed tomographic angiography (CCTA), the coronary artery calcium score (CACS) may be limited in predicting adverse cardiovascular events in asymptomatic diabetic patients. Methods We evaluated the predictive value of CACS for obstructive coronary plaques (OCPs) assessed by CCTA in 328 consecutive asymptomatic patients with type 2 diabetes mellitus who had an estimated glomerular filtration rate greater than 60 ml/min/1.73 m2. Results In total, 29 (9%) patients had OCPs: calcified or mixed OCPs and noncalcified OCPs were found in 26 (8%) and three (1%) patients, respectively. On the basis of a CACS of 0, 1–10, 11–100, and greater than 100, OCPs were found in 2, 5, 15, and 36% of patients, respectively. On receiver operating characteristic curve analysis, the optimal cutoff CACS for predicting OCPs was found to be 33, with 83% sensitivity and 81% specificity (area under the curve, 0.853; 95% confidence interval, 0.777–0.930; P<0.001). Positive and negative predictive values of a CACS of 33 for OCPs were 30 and 98%, respectively. On multivariate logistic regression analysis, age [odds ratio (OR), 1.09], microalbuminuria (OR, 3.43), current smoking (OR, 3.93), and CACS greater than 33 (OR, 15.85) were found to be independently associated with an increased risk for OCPs (P<0.05, respectively). The predictive significance of CACS greater than 33 for OCPs improved after considering the status of microalbuminuria and current smoking. Conclusion These findings suggest that CACS is an effective gatekeeper for evaluating obstructive coronary artery disease using CCTA in asymptomatic Korean patients with type 2 diabetes mellitus who have near-normal kidney function.